A Theology of God-Talk - Allen, J. Timothy, author.
1 online resource (184 pages)
Keywords: Use this common coping mechanism to help people respond to crises!This thoughtful book offers a fresh theological interpretation for the ways people talk about God in times of crisis. A Theology of God-Talk: The Language of the Heart probes the meaning behind phrases like “It must have been God’s will” and “The Lord took Uncle Harry.” Though many caring professionals dismiss such talk as insensitive or irrational, these phrases offer powerful clues to the speaker’s personal religious feelings. A Theology of God-Talk demonstrates the ways that God-talk moves the sufferer through the grief and doubt of the crisis. By recognizing the ways God-talk resembles myth, apocalyptic tale, tragedy, story, and even prayer--all literary categories--the caregiver can begin to help sufferers rewrite their personal narratives in the wake of tragedy. A Theology of God-Talk examines the crucial issues of God-talk, including: common false assumptions about it the theology of God-talk interpretations and misinterpretations how to glean counseling insights from God-talk differing stances for sufferers and survivors of tragedyBringing together psychology, theology, and narrative theory, this insghtful and sensitive book offers new ways of looking at this common reaction to crisis. A Theology of God-Talk is an instant classic and an essential resource for pastors, chaplains, therapists, grief counselors, and theologians.